The marksman - Adams, Marcus; Stevens, Andrew; Spengler, Pierre; Sony Pictures Home Entertainment; Sandstorm Films ([California] : Minotaur Film Partnership No. 2, 2005)
An action-packed, gripping espionage movie starring Wesley Snipes. The U.S. is tricked into targeting an'armed' nuclear reactor captured by Chechen rebels, but a Special Ops team, led by Snipes, figures a way to stop disaster from happening
Title from container
Special features: Scene selections, photo gallery, trailers
Director of photography, Tudor Luciciu ; editor, Masahiro Hirakubo ; music, Barry Taylor ; screenplay by J.S. Cardone & Andy Hurst
Cast: Wesley Snipes, Anthony Warren, Peter Youngblood Hills, William Hope, Warren Derosa
DVD Format
Dolby digital or dolby surround
Keywords: Special forces (Military science) -- United States -- Drama; Espionage -- Drama